2021
DOI: 10.1111/1751-7915.13747
|View full text |Cite
|
Sign up to set email alerts
|

Unlocking the genomic potential of aerobes and phototrophs for the production of nutritious and palatable microbial food without arable land or fossil fuels

Abstract: Renewable H 2 -and CO 2 -derived compounds as novel resource framework for microbial biomass production Food production and the planetary boundaries are already beyond the limits of sustainability (Steffen et al., 2015), yet even more pressure on Earth's carrying capacity is expected with the global population projected to reach 9.2-12.3 billion people by the turn of the century and the rise in living standards (Gerland et al., 2014). Structural changes of the agricultural-based food chain are required to incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 58 publications
0
10
0
1
Order By: Relevance
“…bacteria, algae, yeast and other fungi) for feed or food purposes has been coined 'single cell protein' or 'microbial protein' (MP). Traditionally, the production of MP was predominantly focused on the use of agricultural products or fossil fuels (landand fossil-based) as electron donors and/or carbon sources (Alloul et al 2021). Pikaar et al (2018) showed that MP produced on sugar cane waste (land-and fossilbased) could lower global crop area use, global nitrogen losses from croplands and agricultural greenhouse gas emissions by respectively 10%, 2% and 1%.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…bacteria, algae, yeast and other fungi) for feed or food purposes has been coined 'single cell protein' or 'microbial protein' (MP). Traditionally, the production of MP was predominantly focused on the use of agricultural products or fossil fuels (landand fossil-based) as electron donors and/or carbon sources (Alloul et al 2021). Pikaar et al (2018) showed that MP produced on sugar cane waste (land-and fossilbased) could lower global crop area use, global nitrogen losses from croplands and agricultural greenhouse gas emissions by respectively 10%, 2% and 1%.…”
Section: Introductionmentioning
confidence: 99%
“…Current routes that are being targeted for land-and fossil-free MP production are (phototrophic) microalgae, aerobic hydrogen oxidizing bacteria, methylotrophs or acetotrophs (Alloul et al 2021). Other appealing microbes for MP production are the purple bacteria (PB).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As explained above, the industrial biotechnological applications of MOB are mainly focused on the production of biomass for animal feed formulations [68]. Regarding product quality, a recent study compared the commercial FeedKind® (Calysta, USA) with traditional fishmeal revealing the high potential of M. capsulatus to be used as an alternative protein source in aquaculture [69].…”
Section: Mob Grown On Renewable Energy and Residual Resourcesmentioning
confidence: 99%
“…Genomics is a study of the information structure and function programmed in the genome. Genomics has applications in multiple fields, including medicine (Chen et al, 2018;Lai et al, 2020;Huang et al, 2021), agriculture (Abberton et al, 2016;Parihar et al, 2022), industrial biotechnology (Alloul et al, 2022), synthetic biology (Baltes and Voytas, 2015), etc.…”
Section: Introductionmentioning
confidence: 99%